MODELING OF BIOLOGICAL WASTEWATER TREATMENT ON THE BASIS OF QUICK-COMPUTING NUMERICAL MODEL - Biliaiev, M. M.; Lemesh, M. V. (Science and Transport Progress, 2021)
Purpose. The scientific paper involves the development of quick computing numerical model for prediction of output parameters of aeration tank. The numerical model may be used in predicting the effectiveness of aeration tank under different regimes of work. Methodology. To simulate the process of biological wastewater treatment in aeration tank numerical models were developed. The flow field in the aeration tank is simulated on the basis of potential flow model. 2-D transport equations are used to simulate substrate and sludge dispersion in the aeration tank. To simulate the process of biological treatment simplified model. For the numerical integration of transport equations implicit difference scheme was used. The difference scheme is built for splitting transport equations. Splitting of transport equation into two equations is carried out at differential level. The first equation of splitting takes into account the sludge or substrate movement along trajectories. The second splitting equation takes into account the diffusive process of substrate or sludge. To solve the splitting equations implicit difference scheme was used. For the numerical integration of potential flow equation the implicit scheme of conditional approximation was used. On the basis of constructed numerical model computer experiment was performed to investigate the process of biological treatment in aeration tank. Findings. Quick computing numerical model to simulate the process of biological treatment in the aeration tank was developed. The model can be used to obtain aeration tank parameters under different regimes of work. The developed model takes into account the geometrical form of the aeration tank. Originality. The numerical model which takes into account the geometrical form of aeration tank and fluid dynamics process was developed; the model takes into account substrate and sludge transport in aeration tank and process of biological treatment. Practical value. Efficient numerical model, so called «diagnostic models» was proposed for quick calculation of biological treatment process in aeration tank.